International Handbook of Education for Spirituality, Care and Wellbeing - de Souza, Marian; FRANCIS, LESLIE J.; O'Higgins-Norman, James; Scott, Daniel G. (International Handbooks of Religion and Education, 2009)
Acknowledging and understanding spiritual formation is vital in contemporary education. This book explores the dynamic relationship between education and wellbeing. It examines the theory underpinning the practice of education in different societies where spirituality and care are believed to be at the heart of all educational experiences. The book recognizes that, regardless of the context or type of educational experience, education is a caring activity in which the development of the whole person - body, mind and spirit - is a central aim for teachers and educators in both formal and informal learning. The chapters in this handbook present and discuss topics that focus on spirituality as an integral part of human experience and, consequently, essential to educational programs which aim to address personal and communal identity, foster resilience, empathy and compassion, and promote meaning and connectedness.